The 'Maxillary Pull-through' Technique: A Minimally Invasive Endoscopic-Assisted Approach to Nasal Septum Neoformations with Maxillary Bone Infiltration. Issue 1 (March 2023) - Priore, Paolo; Giovannetti, Filippo; Battisti, Andrea; Di Giorgio, Danilo; Della Monaca, Marco; Raponi, Ingrid; Cassoni, Andrea; Valentini, Valentino
Study Design: Description and validation of a surgical technique. Objective: En-bloc maxillectomy with removal of the nasal septum is a rare procedure; preservation of the nasal bones and integrity of the alveolar ridge is even rarer. These procedures traditionally required a combined transfacial-transoral approach based on lateral rhinotomy. We describe a combined endoscopic transnasal-transoral approach for treatment of nasal septal malignancies that involve the hard palate. Methods: Excision of malignant tumours arising from the nasal septum was achieved in 4 patients using a transnasal-transoral endoscopic approach. Using 4-mm optics angled at 0° and 30°, the septum was freed from the ethmoid and removed en-bloc with the hard palate, by pulling the septum down through the hard palate. Results: Of the 4 patients, 2 underwent complete removal of septal chondrosarcomas, one removal of a sinonasal undifferentiated carcinoma and one removal of a mucoepidermoid carcinoma. In two cases, the palatal mucosa was spared and repositioned to restore separation between the nose and oral cavity. The remaining two cases underwent complete resection of the hard palate; one palate was reconstructed using a pedicled temporalis muscle flap and the other by employing an obturator. No infection was encountered. Partial ethmoidectomy was performed in all four cases. The mean hospital stay was 5 days. All patients are free of disease after a mean follow-up of 4 years (range: 2–7 years). Conclusions: Our new approach allows for minimally invasive resection of nasal septal malignancies that extend to the palate. Our maxillary pull-through technique is a valuable new surgical procedure for malignant pathologies of the nasal septum; the only drawback is that endoscopic surgery has a steep learning curve.